Induction of desiccation tolerance in recalcitrant curry leaf (Murraya koenigii (L.) Sprengel) seed - Arulmoorthy, K.; Raja, K.; Sundareswaran, S. (Journal of Tropical Agriculture, 2022)
Curry leaf is an important leafy vegetable cum spice species grown widely in South India. It is mainly propagated by seeds. But, the seeds possess recalcitrant behavior which is desiccation and freezing sensitive. Also, the seeds have very short shelf life. Therefore, experiments were conducted to induce the desiccation tolerance in the seed by seed treatment for better storage. In this regard, the seeds were soaked in different desiccation tolerance induction chemicals viz., sodium nitroprusside, L-arginine and abscisic acid for 18 h and stored under ambient condition. The results showed that the seed germination (7%) was maintained upto 20 days when the seeds were soaked in abscisic acid at 100 ppm for 18 h. However, untreated control seed lost its viability completely at 10th day of storage.